Stark effect in He I in extremely high electric field - Windholz, Laurentius; Drozdowski, Ryszard; Wąsowicz, Tomasz J.; Kwela, Jerzy (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
In the spectral range between 480–630 nm the Stark effect of the transitions n1Q–21S, n1Q–21P and n3Q–23P (n = 3–10, Q = S, P, D, ...) was studied in atomic helium using electric field up to 1500 kV/cm. For such an extremely high field the Stark splitting becomes greater than the simple structure of the atom. In consequence, anticrossings of the Stark components of the same magnetic quantum number occur. The experimental results have been compared with the theoretical shifts. The results of calculations show good agreement with observation not only for low field values, but also for those in high fields and in the case of level anticrossings.
Optica Applicata, Vol. 36, 2006, nr 4, s. 569-574
Keywords: optyka; Stark effect; helium; electric field